2017
DOI: 10.1039/c6ra27461g
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of metabolite signatures using high-throughput mass spectrometry coupled with multivariate data analysis

Abstract: Disease impacts important metabolic pathways and the alteration of metabolites may serve as a potential biomarker for early-stage diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…[42][43][44][45][46]55,56 A signi-cant increase in multiple phosphatidylcholines (PCs) and a decrease in several specic sphingomyelins (SMs) were observed from tumor to adjacent normal tissue particularly, enhanced levels of choline (C 5 in the MALDI-Fourier transform ion cyclotron resonance mass spectrometry (MALDI-FTICR MS), the potassium or sodium adducts form mechanism of which is the same as the result of this study. 46,58 Different formations of these ions produced are contributed to the different main ionization mechanisms of ESI and DAPCI, which are complementary for compounds identi-cation and potential biomarkers discovery.…”
Section: Differentiation Of Tumor From Adjacent Normal Tissue By Multsupporting
confidence: 49%
“…[42][43][44][45][46]55,56 A signi-cant increase in multiple phosphatidylcholines (PCs) and a decrease in several specic sphingomyelins (SMs) were observed from tumor to adjacent normal tissue particularly, enhanced levels of choline (C 5 in the MALDI-Fourier transform ion cyclotron resonance mass spectrometry (MALDI-FTICR MS), the potassium or sodium adducts form mechanism of which is the same as the result of this study. 46,58 Different formations of these ions produced are contributed to the different main ionization mechanisms of ESI and DAPCI, which are complementary for compounds identi-cation and potential biomarkers discovery.…”
Section: Differentiation Of Tumor From Adjacent Normal Tissue By Multsupporting
confidence: 49%
“…Lipids metabolism makes metabolomics a more promising way to explore these types of diseases as the core issues in CVD. Application of metabolomics in clinical research has provided the chance to obtain new insights into metabolic change and mechanism [62][63][64]. A large amount of information bringing about by metabolomics indicated that these approaches will open a new perspective on disease processes and eventually transit from theory to clinical applications [65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…[126][127][128][129] Numerous studies have also been tested, including early disease detection, treatment prediction and prognosis, monitoring treatment and recurrence testing. [130][131][132][133][134][135][136][137][138][139] Given the extreme complexity of biological mixtures, most MS analytical methods involve the use of LC, GC or CE. However, rapidly growing applications using evolving separation methods and protocols offer opportunities and challenges.…”
Section: Future Perspectivesmentioning
confidence: 99%